Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

staceyyyy1

  • 3 years ago

-112=-8b-7(b+1) show steps please. answer: 7

  • This Question is Closed
  1. jlvm
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    Made a mistake, one sec.

  2. staceyyyy1
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    lol(:

  3. anonymous
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    \[-112=-8b-7b-7\] is the first step, i.e. multiply out using distributive law

  4. jlvm
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    We have: \[-112=-8b-7(b+1)\] Multiply the 7 through: \[-112=-8b-7b-7\] Combine like terms: \[-112=-15b-7\] Multiply everything by -1: \[112=15b+7\] Substract 7: \[105=15b\] Divide by 15: \[7=b\] so, \[b=7\]

  5. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy